FRP FRP CATAMARAN BARGE - KIM, TAEK YOL; LEE, JAE CHEOL (2016)
The present invention relates to an FRP catamaran barge including: a pair of hulls installed on both sides; and a deck connected to the upper part of the pair of hulls. The hull includes: a body having an FRP layer and an inner space; a reinforcing plate formed of the FRP layer and reinforcing the strength of the hull by being installed to divide the inner space; and a filler filling the inner space. The deck has: a composite panel in which the FRP layer is installed in the upper part and the lower part; and a honeycomb panel formed between the composite panels in the upper part and the lower part. According to the present invention, the hull is formed as a catamaran so the FRP catamaran barge has excellent driving performance and excellent stability. The FRP catamaran barge is light and has excellent buoyancy. The RFP catamaran barge has excellent strength so the RFP catamaran barge is not easily deformed. Even if seawater flows into the hull due to damage to the hull, the buoyancy is maintained. So, the FRP catamaran barge is not sunk and is environmentally friendly. Also, when the FRP catamaran barge is scrapped, the FRP catamaran barge can be recycled as other building materials. 본 발명은 양측에 구비된 한쌍의 선체와, 한쌍의 선체의 상부에 결합된 데크를 포함하는 FRP 쌍동 바지선에 있어서, 상기 선체는, FRP층이 포함되고 내부 공간이 형성된 바디와, FRP층으로 이루어지고 상기 내부 공간을 구획하도록 설치되어 선체의 강도를 보강하는 보강판과, 상기 내부 공간에 충진된 충진재를 포함하고, 상기 데크는, 상·하부에는 FRP층이 포함된 복합 판넬이 형성되고, 상·하부의 복합 판넬의 사이에 허니컴 판넬이 형성된 것을 특징으로 하는, FRP 쌍동 바지선을 제공한다. 본 발명에 의하면, 선체가 쌍동선으로 구성되어 주행성과 안정성이 우수하고, 무게가 가볍고 부력이 우수하며, 강도가 우수하여 잘 변형되지 않고, 선체 파손으로 바닷물이 내부로 스며들어도 부력이 그대로 유지되어 침몰 위험이 없으며, 친환경적이고 폐선시 다른 건축 자재로 재활용이 가능한 효과가 있다.